Three-dimensional rockfall modelling and rockfall protection – Port Hills - Avery, MB; Salzmann, H; Teen, A (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
After the February 2011 Christchurch earthquakes Geovert were commissioned by the Canterbury Earthquake Recovery Authority (CERA) to provide the desperately needed answers to the widespread rockfall hazard. Including how best to protect people and assets, how much will it cost and how long will it take. To provide this information Geovert proposed the use of a newly developed state of the art 3D rockfall modelling program which was capable of modelling the vast earthquake affected area in the Christchurch Port Hills. The modelling focused on possible remedial options and their costs, and associated construction programmes, to provide supplementary information to the current Christchurch City Council (CCC) commissioned Geological and Nuclear Sciences (GNS) reports. The outcomes of the modelling were to assist CERA in making critical decisions relating to areas where rockfall hazard exists and where protective works may effectively reduce the this hazard. The 3D modelling was carried by a subconsultant to Geovert Ltd using Hy-Stone, a specialist rockfall modelling programme from the University of Milan in Italy with data for the modelling supplied by CERA, CCC and GNS. This data is the same data used by other consultants commissioned by CERA and CCC in an attempt to better understand the issues affecting the Port Hills. Hy−Stone is a rockfall modelling software utilising numerical code to analyse rockfalls, the related hazard and the associated risk. While a number of remedial options were considered as part of the study it was immediately evident that the most appropriate solution to the hazard was the installation of rockfall barriers. While some areas were better suited to earth bunds, very few locations were treatable at source. Typical results indicated energies were in the order of 1,000 to 2,000 kJ with relatively low bounce heights (less than 3–4 m high). Treatment of this level of energy is relatively straight forward with proprietary products readily available. While the extent of the rockfall issue surrounding the Christchurch earthquakes is phenomenal, the requirements for rockfall protection are by no means exceptional on a global level.